Periódicos eletrônicos brasileiros de economia: acesso nas fontes eletrônicas SciELO, Portal de Periódicos da CAPES e Portal Livre CNEN - SOUSA, Alcione Cardoso de (2017)
Displays electronic journals with free access in economics, in electronic sources SciELO, Portal de Periódicos da CAPES and Portal Livre da CNEN. It emphasizes the importance of knowing these sources. Speaks of the origin of scientific journals and its evolution over time. It presents concepts and definitions of various authorities with extensive experience in this subject. Talks about the history of the economy, its first theoreticians, the etymology of the word (economy) employs the quantitative and descriptive method of journals of this area of knowledge. Explicita through tables, charts and graphs, the quantitative aspects of the research. It recommends that the scholars of this theme, the use of electronic sources with free access in the recovery, organization and dissemination of information in the interim, in order to facilitate the search need the same (reliable information). It concludes that it is imperative to be well informed, for taking macro/micro-economic decisions in the new global order, where power relations are settled in economic power (capital) individually or collectively, and especially international relations. Notes in the three aforementioned sources a universe of sixty (60) titles, including exclusive and coincide. It lists the titles matched for counting purposes, count only once coming to the actual number of thirty-eight (38) titles. And of these, seventeen (17) titles are those which are repeated, while twenty-one (21) are unique. That is, they are recovered in a specific source.